2015
DOI: 10.1186/s12905-016-0287-5
|View full text |Cite
|
Sign up to set email alerts
|

Anemia among indigenous women in Brazil: findings from the First National Survey of Indigenous People’s Health and Nutrition

Abstract: BackgroundAnemia is recognized as a major public health problem that disproportionately affects vulnerable populations. Indigenous women of reproductive age in Brazil are thought to be at high risk, but lack of nationwide data limits knowledge about the burden of disease and its main determinants. This study aimed to assess the prevalence of anemia and associated factors in this population using data from The First National Survey of Indigenous People’s Health and Nutrition in Brazil.MethodsData were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
1
6
0
5
Order By: Relevance
“…In contrast, the same study also showed low height-for-age (stunting) in children < 5 was most prevalent in the North (40.8%) and least in the Northeast (13.9%), with significant determinant factors including region, socioeconomic status, access to sanitation services, and prior hospitalization (Horta et al 2013). Women's and children's anemia were higher in the North (46.3% and 66.4%, respectively) and lower in the Northeast (22.8% and 41.1%, respectively) (Borges et al 2016;Leite et al 2013). These results suggest a double burden of malnutrition among Indigenous peoples in Brazil, with the South/Southeast most burdened by obesity and anemia in adults (Borges et al 2016;Coimbra et al 2020) and the North most burdened by stunting and anemia in children under five years (Horta et al 2013;Leite et al 2013).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, the same study also showed low height-for-age (stunting) in children < 5 was most prevalent in the North (40.8%) and least in the Northeast (13.9%), with significant determinant factors including region, socioeconomic status, access to sanitation services, and prior hospitalization (Horta et al 2013). Women's and children's anemia were higher in the North (46.3% and 66.4%, respectively) and lower in the Northeast (22.8% and 41.1%, respectively) (Borges et al 2016;Leite et al 2013). These results suggest a double burden of malnutrition among Indigenous peoples in Brazil, with the South/Southeast most burdened by obesity and anemia in adults (Borges et al 2016;Coimbra et al 2020) and the North most burdened by stunting and anemia in children under five years (Horta et al 2013;Leite et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…Women's and children's anemia were higher in the North (46.3% and 66.4%, respectively) and lower in the Northeast (22.8% and 41.1%, respectively) (Borges et al 2016;Leite et al 2013). These results suggest a double burden of malnutrition among Indigenous peoples in Brazil, with the South/Southeast most burdened by obesity and anemia in adults (Borges et al 2016;Coimbra et al 2020) and the North most burdened by stunting and anemia in children under five years (Horta et al 2013;Leite et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…In Brazil, data from the National Child and Women's Demographic and Health Survey (Pesquisa Nacional de Demografia e Saúde da Criança e da Mulher -PNDS) 2006 show that 29.4% of women aged 15 to 49 years had anemia, while the prevalence in children was 20.9% 7 . Studies with the female population of childbearing age reveal anemia prevalence ranging from 18.6% in women in the municipality of Pernambuco 11 to 38.0% in indigenous women 12 . In pregnant women users of Basic Health Units of Maceió, the prevalence was 28.3% in 2014 13 .…”
Section: Palavras-chavementioning
confidence: 99%
“…This study identified a significant increase in the number of breastfeeding-related consultations for babies under one year old after the intervention, highlighting the importance of training for the improvement of the information system, which is essential for planning actions in communities. It was demonstrated that breastfeeding extends beyond six months of age, which can be a factor contributing to the high degree of child malnutrition in the population (Borges et al 2016) in territories where there is inadequate monitoring of the introduction of solid foods into a child's diet. Pantoja et al (2014) report that the nutritional deficits found in their research were the worst described to date in the Brazilian literature on indigenous populations, pointing to a situation of chronic malnutrition that requires urgent attention.…”
Section: Discussionmentioning
confidence: 99%